The “Themis Group” of Euphaedra Hübner, [1819] in Angola. Revision and description of one new species (Lepidoptera: Nymphalidae, Limenitidinae) - A. Bivar-de-Sousa; L. F. Mendes (SHILAP, 2023)
New data are presented relatively to the Euphaedra Hübner, [1819], subgenus Euphaedrana Hecq, 1976 of the “group themis” in Angola. Four species are assigned being one of them described as new with base on specimens from the Cabinda Territory.